2010
DOI: 10.1038/cgt.2010.13
|View full text |Cite|
|
Sign up to set email alerts
|

Bleomycin/interleukin-12 electrochemogenetherapy for treating naturally occurring spontaneous neoplasms in dogs

Abstract: On the basis of superior outcomes from electrochemogenetherapy (ECGT) compared with electrochemotherapy in mice, we determined the efficacy of ECGT applied to spontaneous canine neoplasms. Intralesional bleomycin (BLM) and feline interleukin-12 DNA injection combined with translesional electroporation resulted in complete cure of two recurrent World Health Organization stage T 2b N 0 M 0 oral squamous cell carcinomas (SCCs) and one T 2 N 0 M 0 acanthomatous ameloblastoma. Three remaining dogs, which had no oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…However, this mechanism leads to the apoptotic death of tumor cells resulting in a high tumoricidal effect with good cosmetic results (minimal scar tissue formation in the treated patients). A final advantage of electrochemotherapy is the possible modulation of the immune system, probably through the uncovering of cancer antigens, as suggested by studies showing a synergy with interleukin 2 or 12 [51,52]. Furthermore, our investigations on companion animals with spontaneous cancer evidenced a clonal selection of the neoplasms treated with electrochemotherapy and longer survival in dogs with melanoma that developed vitiligo-like lesions at the tumor site after electroporation [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism leads to the apoptotic death of tumor cells resulting in a high tumoricidal effect with good cosmetic results (minimal scar tissue formation in the treated patients). A final advantage of electrochemotherapy is the possible modulation of the immune system, probably through the uncovering of cancer antigens, as suggested by studies showing a synergy with interleukin 2 or 12 [51,52]. Furthermore, our investigations on companion animals with spontaneous cancer evidenced a clonal selection of the neoplasms treated with electrochemotherapy and longer survival in dogs with melanoma that developed vitiligo-like lesions at the tumor site after electroporation [53].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure yielded a blood IL-12 level greater than 100 pg/mL [47]. The electroporation parameters for intramuscular injection, which had previously been identified as optimal, were set at 350 V/cm and 20 ms pulse duration for 2 pulses [46].…”
Section: Methodsmentioning
confidence: 99%
“…Once the pDNA reaches the cell's nucleus, the production of the protein encoded by the plasmid ensues . In vivo electroporation does not cause any severe adverse events, and several canine and human clinical trials showed the safety and clinical efficacy of electroporation‐mediated intratumoural delivery of a pDNA encoding IL‐12 . Those studies present evidence that it is possible to overcome local suppressor pathways in tumours and tip the balance in favour of an antitumour immune response.…”
Section: Introductionmentioning
confidence: 94%